Dual beneficial effects of (-)-epigallocatechin-3-gallate on levodopa methylation and hippocampal neurodegeneration: in vitro and in vivo studies. - Ki Sung Kang; Yujing Wen; Noriko Yamabe; Masayuki Fukui; Stephanie C Bishop; Bao Ting Zhu (PLoS ONE, 2010)
A combination of levodopa (L-DOPA) and carbidopa is the most commonly-used treatment for symptom management in Parkinson's disease. Studies have shown that concomitant use of a COMT inhibitor is highly beneficial in controlling the wearing-off phenomenon by improving L-DOPA bioavailability as well as brain entry. The present study sought to determine whether (-)-epigallocatechin-3-gallate (EGCG), a common tea polyphenol, can serve as a naturally-occurring COMT inhibitor that also possesses neuroprotective actions.Using both in vitro and in vivo models, we investigated the modulating effects of EGCG on L-DOPA methylation as well as on chemically induced oxidative neuronal damage and degeneration. EGCG strongly inhibited human liver COMT-mediated O-methylation of L-DOPA in a concentration-dependent manner in vitro, with an average IC50 of 0.36 microM. Oral administration of EGCG moderately lowered the accumulation of 3-O-methyldopa in the plasma and striatum of rats treated with L-DOPA+carbidopa. In addition, EGCG also reduced glutamate-induced oxidative cytotoxicity in cultured HT22 mouse hippocampal neuronal cells through inactivation of the nuclear factor kappaB-signaling pathway. Under in vivo conditions, administration of EGCG exerted a strong protective effect against kainic acid-induced oxidative neuronal death in the hippocampus of rats.These observations suggest that oral administration of EGCG may have significant beneficial effects in Parkinson's patients treated with L-DOPA and carbidopa by exerting a modest inhibition of L-DOPA methylation plus a strong neuroprotection against oxidative damage and degeneration.